DIVERSITY AND BIOCHEMICAL PROPERTIES OF MICROORGANISMS ISOLATED FROM THE FISH GUT - Hamidova Saodat Khikmatovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. The world’s resources of seafood and freshwater fish are not unlimited, therefore, over the past century, interest in aquaculture has increased so much, that is, the breeding and cultivation of fish, algae, mollusks, and crustaceans. A positive factor is non-waste, which makes it possible to produce products for feeding farm animals, for example, fishmeal, from the waste of the fishing industry.